2015
DOI: 10.4018/978-1-4666-7248-2.ch022
|View full text |Cite
|
Sign up to set email alerts
|

A New Robust H∞ Control Power

Abstract: Attention has been paid by many researchers to address the various challenges of grid connection of DFIG-based Wind Energy Conversion Systems (WECS). This chapter focuses on the design of a robust H8 controller for the power flow between the stator of the Doubly-Fed Induction Generator (DFIG) and the grid. The robust H8 controller design is formulated as a mixed-sensitivity problem. A mathematical model of the DFIG written in an appropriate d-q reference frame is established to carry out simulations. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…4 explains the SM-H∞ control structure. Robust H∞ control issue has been examined widely in recent years [32,33]. It is an important solution for system disturbances and uncertainties [34].…”
Section: Sliding Mode H∞ Controllermentioning
confidence: 99%
“…4 explains the SM-H∞ control structure. Robust H∞ control issue has been examined widely in recent years [32,33]. It is an important solution for system disturbances and uncertainties [34].…”
Section: Sliding Mode H∞ Controllermentioning
confidence: 99%
“…In order to regulate the power of the DFIG based wind turbine system, the vector control strategy is used. It consists of using the flux orientation, such as stator flux orientation (SFO) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]: ܸ ௦ௗ ൌ 0 and ܸ ௦ ൌ ܸ ௦ ൌ ߱ ௦ ߮ ௦ . The active and reactive powers at the stator side and rotor side of the DFIG are given as:…”
Section: B Modeling Of the Doubly-fed Induction Generatormentioning
confidence: 99%
“…The obtained simulation results were satisfactory, showing the robustness of the H ஶ compared to the conventional PI controller. Recently, a robust power command based on the Active Disturbance Rejection Control (ADRC) for DFIG used in a WECS system has been designed in [14]. Simulation results showed that the proposed ADRC controller had the best performance in terms of robustness against machine's parameter variations.…”
Section: Introductionmentioning
confidence: 99%